OS 34-03 THE ASSOCIATION OF TETRAHYDROBIOPTERIN WITH A MARKER OF NITRIC OXIDE PRODUCTION IN A BLACK AND WHITE POPULATION: THE SABPA STUDY. (September 2016) - Huisman, Hugo; Schutte, Aletta; Van Rooyen, Johannes; Fourie, Carla; Kruger, Ruan; Smith, Wayne; Lammertyn, Leandi; Malan, Leone; Botha, Shani; Mels, Carina
Abstract : Objective: Tetrahydrobiopterin (BH4) is a cofactor for nitric oxide synthase (NOS) and may be a critical agent in endothelial function by improving nitric oxide (NO) mediated effects. It is reported that the NO synthesis capacity seems favourable in blacks despite their adverse cardiovascular profile. We therefore compared the concentrations of BH4, as well as blood pressure (BP) and arterial stiffness between black and white teachers. Furthermore, we tested the associations of BH4 with a product and inhibitor of NO synthesis, namely L-citrulline, and symmetric dimethylarginine (SDMA) respectively, in both ethnic groups. Design and Method: This cross-sectional sub-study is embedded in the SABPA study. The participants were stratified by race (black n = 194, white n = 204). Cardiovascular measurements included blood pressure (BP) and pulse wave velocity (PWV). Biochemical analyses of BH4, L-citrulline and SDMA were determined by recognised biochemical methods. Results: Although blacks had higher BP and PWV (p < 0.05), their BH4 levels also tended to be higher (p = 0.07) compared to whites. In whites positive correlations existed with single, partial (adjusted for age, sex and BMI) and multiple regression of BH4 with L-citrulline (adj.R 2  = 0.20, β = 0.17, p = 0.01) and a negative correlation with SDMA (adj.R 2  = 0.20, β = −0.15, p = 0.03). In single, partial and multiple regression analyses we found a positive correlation between BH4 and SDMA (adj.R 2  = 0.12, β = 0.23, p = 0.003) in black participants. Conclusions: In white teachers BH4 independently associated with L-citrulline, a product of NO synthesis while no such correlation was found in black teachers. Instead an association of BH4 with SDMA, indicating an inhibition of NOS was indicated. Our result suggests a suppressed endothelial function in the black group and this is in line with the higher prevalence of hypertension known in this population.